2022
DOI: 10.1136/bmjopen-2021-054271
|View full text |Cite
|
Sign up to set email alerts
|

Anti-SARS-CoV-2 antibodies among indigenous populations of the Brazilian Amazon: a cross-sectional study

Abstract: ObjectivesThe emergence of SARS-CoV-2 and its pandemic spread generated serious concern about the impact of the infection on vulnerable indigenous populations of the Brazilian Amazon. Thus, this study aimed to perform a seroepidemiological survey of anti-SARS-CoV-2 antibodies in those populations.SettingSix indigenous ethnic groups living in the State of Pará (Northern Brazil) were investigated. The villages of Xikrin do Bacajá, Assurini, Araweté, Parakanã, Munduruku and Kararaô were visited from October 2020 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
0
8
1
Order By: Relevance
“…Compared to surveys conducted in Brazil around mid-2021 the seroprevalence of antibodies against SARS-CoV-2 in our sample (53.61%) was higher than other studies reported in the South and Southeast regions of Brazil ( 14 , 16 , 17 ), being closer to rates observed at that time in the North region ( 18 , 19 ) and in indigenous populations ( 20 , 21 ). With a vaccine coverage of 37% in our study population, the large difference in seroprevalence between vaccinated (90.5%) and unvaccinated (31%) residents confirmed findings from other studies ( 22 ) of how vaccination decisively contributes to the population's immunity, even in an area with a high prevalence of infection-induced antibodies after exposure to a pandemic for more than a year.…”
Section: Discussioncontrasting
confidence: 72%
“…Compared to surveys conducted in Brazil around mid-2021 the seroprevalence of antibodies against SARS-CoV-2 in our sample (53.61%) was higher than other studies reported in the South and Southeast regions of Brazil ( 14 , 16 , 17 ), being closer to rates observed at that time in the North region ( 18 , 19 ) and in indigenous populations ( 20 , 21 ). With a vaccine coverage of 37% in our study population, the large difference in seroprevalence between vaccinated (90.5%) and unvaccinated (31%) residents confirmed findings from other studies ( 22 ) of how vaccination decisively contributes to the population's immunity, even in an area with a high prevalence of infection-induced antibodies after exposure to a pandemic for more than a year.…”
Section: Discussioncontrasting
confidence: 72%
“…Difficulties in access to healthcare, along with characteristics of social organization and genetic susceptibilities intrinsic to indigenous peoples, may have contributed to these outcomes. 4 , 38…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of new infectious agents among indigenous groups is alarming due to the potentially lower variability of immune response and other genetic susceptibilities, leading to increased disease severity and mortality. 4 In addition, cultural aspects such as the social organization in indigenous villages may challenge physical distancing measures and facilitate the spread of SARS-CoV-2. 3 Economic activities in indigenous lands, such as commercial agriculture, mining, and road constructions, increased under Bolsonaro's government in Brazil, exponentiating the likelihood of exposure of indigenous populations to the virus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Numerous seroprevalence studies have been conducted in the Latin American region, both population-based studies and studies focusing on specific populations (healthcare (HCW) or first-line workers, prison workers, indigenous populations, elderly populations, etc). [4][5][6][7][8][9][10][11][12][13][14][15] The reported seroprevalence is highly heterogenous between studies (10,4% -68,1 %), varying by study population, characteristics of the COVID-19 epidemic at the time of sampling, and differences in sociodemographic factors. [4][5][6][7][8][9][10][11][12][13][14][15] Factors associated with increasing risk of seropositivity include ethnicity (indigenous or Afro-descent), presence of COVID-19 symptoms, past history of COVID-19 or close contacts, lower educational level, and working night shifts (for HCW) or in a prison.…”
Section: Introductionmentioning
confidence: 99%